Identification of Antibiotics in Surface-Groundwater. A Tool towards the Ecopharmacovigilance Approach: A Portuguese Case-Study - Paula Viana; Leonor Meisel; Ana Lopes; Rosário de Jesus; Georgina Sarmento; Sofia Duarte; Bruno Sepodes; Ana Fernandes; Margarida M. Correia dos Santos; Anabela Almeida; M. Conceição Oliveira (Antibiotics, 2021)
Environmental monitoring, particularly of water, is crucial to screen and preselect potential hazardous substances for policy guidance and risk minimisation strategies. In Portugal, extensive data are missing. This work aimed to perform a qualitative survey of antibiotics in surface- groundwater, reflecting demographic, spatial, consumption and drug profiles during an observational period of three years. A passive sampling technique (POCIS) and high-resolution chromatographic system were used to monitor and analyse the antibiotics. The most frequently detected antibiotics were enrofloxacin/ciprofloxacin and tetracycline in surface-groundwater, while clarithromycin/erythromycin and sulfamethoxazole were identified only in surface water. The detection of enzyme inhibitors (e.g., tazobactam/cilastatin) used exclusively in hospitals and abacavir, a specific human medicine was also noteworthy. North (Guimarães, Santo Tirso and Porto) and South (Faro, Olhão and Portimão) Portugal were the regions with the most significant frequency of substances in surface water. The relatively higher detection downstream of the effluent discharge points compared with a low detection upstream could be attributed to a low efficiency in urban wastewater treatment plants and an increased agricultural pressure. This screening approach is essential to identify substances in order to perform future quantitative risk assessment and establishing water quality standards. The greatest challenge of this survey data is to promote an ecopharmacovigilance framework, implement measures to avoid misuse/overuse of antibiotics and slow down emission and antibiotic resistance.